The Role of m6A RNA Methylation in Cancer: Implication for Nature Products Anti-Cancer Research - Song, Na; Cui, Kai; Zhang, Ke; Yang, Jie; Liu, Jia; Miao, Zhuang; Zhao, Feiyue; Meng, Hongjing; Chen, Lu; Chen, Chong; Li, Yushan; Shao, Minglong; et al. (Frontiers in Pharmacology, 2022)
N6-methyladenosine (m6A) RNA methylation is identified as the most common, abundant and reversible RNA epigenetic modification in messenger RNA (mRNA) and non-coding RNA, especially within eukaryotic messenger RNAs (mRNAs), which post-transcriptionally directs many important processes of RNA. It has also been demonstrated that m6A modification plays a pivotal role in the occurrence and development of tumors by regulating RNA splicing, localization, translation, stabilization and decay. An increasing number of studies have indicated that natural products have outstanding anti-cancer effects with their unique advantages of high efficiency and minimal side effects. However, at present, there are very few research articles to study and explore the relationship between natural products and m6A RNA modification in tumorigenesis. m6A is dynamically deposited, removed, and recognized by m6A methyltransferases (METTL3/14, METTL16, WTAP, RBM15/15B, VIRMA, CBLL1 and ZC3H13, called as “writers”), demethylases (FTO and ALKBH5, called as “erasers”), and m6A-specific binding proteins (YTHDF1/2/3, YTHDC1/2, IGH2BP1/2/3, hnRNPs, eIF3 and FMR1, called as “readers”), respectively. In this review, we summarize the biological function of m6A modification, the role of m6A and the related signaling pathway in cancer, such as AKT, NF-kB, MAPK, ERK, Wnt/β-catenin, STAT, p53, Notch signaling pathway, and so on. Furthermore, we reviewed the current research on nature products in anti-tumor, and further to get a better understanding of the anti-tumor mechanism, thus provide an implication for nature products anti-cancer research by regulating m6A modification in the future.